Biopolitical Control and Subjectivity in Aslam’s The Golden Legend and Hamid’s Exit West - Ejaz, Rimsha; Shaheen, Aamer; Qamar, Sadia (Pakistan Languages and Humanities Review, 2024)
This research paper, by applying Michel Foucault’s concept of biopolitics, offers a Foucauldian analysis of two contemporary novels: Mohsin Hamid’s Exit West (2017) and Nadeem Aslam’s The Golden Legend (2017) in order to examine the relations between biopolitics and subjectivity. Using Michel Foucault’s lens, this research paper looks at how these novels represent the ways in which power is used over bodies and people. It also analyzes how the main characters’ lives are affected by governmental tools, organizations, and technologies. The study of biopolitics in these novels throws light on how the characters discuss their lives in environments marked by political change and migration, including the handling and management of bodies. The research further investigates the development and modification of subjectivity under the setting of biopolitical governance. By exploring the nuances of power methods that form the characters’ impressions of both themselves and other people, it investigates the relationship that exists between individual agency and the larger systems of power. The research paper attempts to further the discussion on the incorporation of political and philosophical topics in contemporary fiction. The research paper examines the complexities of biopolitics and subjectivity as they appear in these novels, revealing valuable insights into the ways in which contemporary Pakistani Anglophone fiction both depicts and resists the current socio-political landscape.